Pengaruh Reinforcement dalam Mengurangi Perilaku Negatif pada Anak Gangguan Perilaku - Firdiana, Melly Syahara; Tiahirani, Novi; Bengi, Nabila Simah; Anisa, Anisa; Ariska, Nadia; Safaruddin, Safaruddin (Jurnal Pendidikan Kebutuhan Khusus, 2020)
This research is motivated by a problem found in children who experience difficulties in social behavior, namely often leaving the classroom without a clear purpose. This study aims to change the behavior of children which can interfere with the teaching and learning process in school. The research method used was Single Subject Reserch (SSR) through positive reinforcement with the design of A-B-A, A (baseline) before intervention. B (intervention) and A are the results of intervention. The results showed changes in behavior of children. The initial research recorded the highest score reaching 11 times to get out of the class and the final result was a significant change, with a stable score estimated at four and the lowest score in the second place. Suggestion Researchers to teachers to use positive reinforcement in changing children's behavior.